Socio-Demographic and Preoperative Clinical Factors Associated With 5-Year Weight Trajectories After Roux-en-Y Gastric Bypass and Sleeve Gastrectomy - Sahil Patel, MD; Chen Jiang, PhD; Brandon Cowan, MD; Jie Yin, MS; Catherine Schaefer, PhD; Sanjoy Dutta, MD; Rouzbeh Mostaedi, MD; Hélène Choquet, PhD (Annals of Surgery Open)
Objective:. To determine whether socio-demographic and preoperative clinical factors contribute to the percent total body weight loss (%TBWL) after bariatric surgery (BS). Background:. BS is the most effective long-term treatment for medically complicated obesity. More information is needed about the factors that contribute to postoperative %TBWL in large and ethnically diverse cohorts. Methods:. This retrospective study conducted in the Kaiser Permanente Northern California region included 7698 patients who underwent Roux-en-Y gastric bypass (RYGB) or sleeve gastrectomy (SG) between January 2009 and March 2015. Trajectory analyses were conducted from 5-year follow-up data to assign patients to “low,” “average,” or “high” postoperative %TBWL groups. We then evaluated whether age, sex, race/ethnicity, neighborhood deprivation index and preoperative body mass index (BMI)/weight loss, diabetes, hypertension, and sleep apnea contributed to postoperative %TBWL using logistic regression models. Results:. Of 7698 patients (83.2% women), 48.6% underwent a RYGB and 51.4% underwent a SG. Postoperative %TBWL trajectories over 5 years were obtained in 6229 (81%) of 7698 eligible patients. About 27.8% and 29.3% of patients followed the “low” postoperative %TBWL trajectory, for RYGB and SG, respectively. Men, older patients, and Asian, Black, and Hispanic/Latino patients were more likely to be classified in the low postoperative %TBWL group. Patients showing lower postoperative %TBWL had a lower preoperative BMI (but lost less weight before surgery) and were more likely to have preoperative comorbidities. Conclusions:. This study confirms and extends prior findings of the effects of several demographic and preoperative clinical factors on postoperative weight loss. Findings could improve the support of patients to achieve desired surgical outcomes.